Síntese de novos adutos de Morita-Baylis-Hillman: bioisosterismo clássico na otimização de leishmanicidas - Silva, Fábio Pedrosa Lins (2009)
This work was designed using the concept of classical bioisosterism where isoelectronic OH groups were replaced by the CH3 group, aimed at finding a relationship between the lipossolubility of the adducts Morita-Baylis-Hillman (AMBH) and its biological activity. Was developed in this work, synthetic methodologies for the preparation of 16 AMBH unprecedented (47-62), getting good and high yields. Initially was synthesized AMBH 8 using the 2-hydroxyethyl Acrylate 45 as Michael acceptor, giving the adducts 47 (2-hydroxyethyl [2-(hydroxy( 2-nitrophenyl)methyl)] acrylate, 71%), 48 (2-hydroxyethyl [2-(hydroxy( 3-nitrophenyl)methyl)] acrylate, 50%), 49 (2-hydroxyethyl [2-(hydroxy(4- nitrophenyl)methyl)] acrylate, 62%), 50 (2-hydroxyethyl [2-(hydroxy(pyridin-2- yl)methyl)] acrylate, 94%), 51 (2-hydroxyethyl [2-(hydroxy(pyridin-3-yl) methyl)] acrylate, 83%), 52 (2-hydroxyethyl [2-(hydroxy(pyridin-4-yl)methyl)] acrylate, 80%), 53 (2-hydroxyethyl [2-((4-bromophenyl)(hydroxy)methyl)] acrylate, 67%), 54 (2-hydroxyethyl [2-(hydroxy(naphthalen-2-yl)methyl)] acrylate, 71%). The second step of the synthesis was the preparation of Propyl Acrylate (46), from acrylic acid and propanol (yield 98%), which was later used as Michael acceptors in the synthesis of AMBH 55 (Propyl [2-(hydroxy(2-nitrophenyl) methyl)] acrylate, 68%), 56 (Propyl [2-(hydroxy(3-nitrophenyl)methyl)] acrylate, 73%), 57 (Propyl [2-(hydroxy(4-nitrophenyl)methyl)] acrylate, 97%), 58 (Propyl [2-(hydroxy(pyridin-2-yl)methyl)]acrylate, 70%), 59 (Propyl [2- (hydroxy(pyridin-3-yl)methyl)acrylate], 80%), 60 (Propyl [2-(hydroxy(pyridin-4- yl)methyl)] acrylate, 66%), 61 (Propyl [2-((4-bromophenyl)(hydroxy)methyl)] acrylate, 64%), 62 (Propyl [2-(hydroxy(naphthalen-2-yl)methyl)] acrylate, 60%). All of these adducts were bioavailiated in vitro against the parasite Leishmania amazonensis, their cytotoxicity in macrophages were studied and their therapeutic indices calculated. Unlike expected, the bioisosteric modification not presented a direct relationship between the lipossolubility (Log P) of these compounds and their biological activity. All adducts showed strong activity antipromastigote, being the compounds 47, 55, 49, 57, 53, 54 and 62 the most actives in L. amazonensis, all with IC50 less than 60μM. Among them the AMBH 47 was the most active and that presented the higher therapeutic index, which is the prototype substance of this work.